Duodenal nodular lymphoid hyperplasia in a patient with IgA deficiency. Issue 12 (8th September 2020) - Ida, Hanae; Maruyama, Dai; Maeshima, Akiko Miyagi; Kamiya, Takahiro; Morio, Tomohiro; Izutsu, Koji
Abstract: Most patients with IgA deficiency are asymptomatic, but duodenal nodular lymphoid hyperplasia is one symptom known to be associated with common variable immunodeficiency (CVID), including selective IgA deficiency and agammaglobulinemia. Abstract : Most patients with IgA deficiency are asymptomatic, but duodenal nodular lymphoid hyperplasia is one symptom known to be associated with common variable immunodeficiency (CVID), including selective IgA deficiency and agammaglobulinemia.